Analysis of the Anti-Tumour Effect of Xuefu Zhuyu Decoction Based on Network Pharmacology and Experimental Verification in Drosophila - Wang, Sitong; Wu, Chenxi; Li, Yinghong; Ye, Bin; Wang, Shuai; Li, Guowang; Wu, Jiawei; Liu, Shengnan; Zhang, Menglong; Jia, Yongsen; Cao, Huijuan; Jiang, Chunhua; et al. (Frontiers in Pharmacology, 2022)
Background: Tumours are among the most lethal diseases that heavily endanger human health globally. Xuefu Zhuyu Decoction (XFZYD) is a prescription used to treat blood-activating stasis. Although XFZYD has been shown to suppress migration and invasion of tumour cells, the active ingredients, potential targets, and underlying mechanism remain largely elusive. Purpose: To identify the prospective ingredients and major targets of XFZYD against tumours, and evaluate the efficacy and potential molecular mechanisms of XFZYD extract on tumour growth and invasion Methods: We predicted that XFZYD might act on 80 targets through 128 active components using the network pharmacology analysis method. In addition, we prepared an XFZYD aqueous extract and employed the RasV12/lgl-/--induced Drosophila tumour model to carry out experimental verification. Results: XFZYD did not exhibit any side effects on development, viability, and fertility. Furthermore, XFZYD significantly impeded tumour size and invasion at moderate concentrations and suppressed the increased phosphorylation of JNK but strongly enhanced the expression of Caspase3 in the RasV12/lgl-/- model. Finally, the mRNA level of the transcription complex AP-1 component c-FOS was remarkably reduced. In contrast, the transcription of three pro-apoptotic genes was significantly increased when XFZYD was used to treat the tumour model. Conclusion: The study findings suggest that XFZYD may promote tumour cell apoptosis by activating caspase signalling to control primary growth and hinder tumour cell invasion by suppressing JNK/AP-1 signalling activity, thus providing a potential therapeutic strategy for XFZYD in the clinical treatment of cancer and other related diseases.